Development and validation of high-performance liquid chromatographic method for determination of ofloxacin and lomefloxacin in human plasma - Zendelovska Dragica; Stafilov Trajče (Journal of the Serbian Chemical Society, 2005)
Ahigh-performance liquid chromatographicmethod for the determination of ofloxacin and lomefloxacin in human plasma has been developed and validated. The effect of organic modifiers on the retention of the investigated drugs was investigated. A simple isocratic chromatographic assay with UV-detection at 280nm was performed on a Hibar Lichrospher 100 RP 8 column (250x4.6mm 5μm. Merck, Germany) using a mixture of acetonitrile and 0.5 % triethylamine in water (pH adjusted to 2.5 with H3PO4) (15:85, V/V) as the mobile phase at flow rate of 1.2 mL min-1. The calibration curves were linear in the concentration ragne of 0.5-6.0μg mL-1 for ofloxacin and 0.2-4.5 μg mL-1 for lomefloxacin.